PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH DAN MOTIVASI TERHADAP KETERAMPILAN KEWARGANEGARAAN SISWA SEKOLAH DASAR - Asnawita; Mohammad Imam Farisi; Rini Farmila Yanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of the Problem-Based Learning (PBL) model and learning motivation on the citizenship skills of fifth grade elementary school students. However, conventional learning which is still dominant causes low student involvement in learning, thus inhibiting the development of these skills. The PBL model was chosen as an innovative approach to overcome this problem. This study uses a quantitative method with an experimental design. Data were obtained through citizenship skills tests, learning motivation questionnaires, and observations of student activities. The instruments of this study were questionnaires and tests. The questionnaire was used to see students' learning activities and the test was used to see students' high-level thinking skills. The data analysis technique used normality and homogeneity tests as prerequisite tests, t-tests for hypotheses one, two, three and two-way ANOVA tests for the fourth hypothesis. Based on the research results obtained: (1). There is an influence of the Problem-Based Learning model on the Civic Skills of Elementary School Students as evidenced by the results of the t-test at the sig. (2-tailed) level of 0.05 obtained a sig. value of 0.019 where the value of 0.019 <0.05, (2). There is an influence of the High Motivation Influence on the Civic Skills of Elementary School Students as evidenced by the results of the t-test obtained a sig. value of 0.005 <0.05, (3) There is an influence of the Low Motivation Influence on the Civic Skills of Elementary School Students as evidenced by the results of the t-test obtained a sig. value of 0.011 <0.05, and (4) The results of the calculation of the fourth hypothesis test using the two-way ANOVA test showed a significance of the test results of 0.234 >0.05, then H0 is accepted, meaning there is no influence of the Problem-Based Learning Model and Motivation on the Civic Skills of Elementary School Students. Keywords: Problem-Based Learning, Learning Motivation, Civic Skills, Elementary Education